Alkaline hydrothermal treatment of P25 titanium dioxide for low temperature sintering of Li2TiO3 tritium breeding ceramics - Yichao Gong; Yuefei Wang; Junjie Li; Fei Han; Mao Deng; Qingze Na; Yijiang Yang; Zhanwen Liu; Mingxiang Tang; Chao Dang; Guojun Zhang (Nuclear Materials and Energy, 2022)
For solid tritium breeding materials, a high sintering temperature is essential to achieve satisfactory density, high crushing load, favorable physical and chemical properties, while lithium volatilization and grain coarsening occur at higher sintering temperature, which are not conducive to tritium production and release. Therefore, low temperature sintering of lithium containing ceramics needs to be studied. In this work, P25 titanium dioxide was hydrothermally treated in alkaline solution, and then used as titanium source to prepare Li2TiO3 ceramics. The prepared Li2TiO3 ceramics exhibit uniform and dense microstructure and extremely high crushing load (a.v. 78.93 ∼ 83.98 N) at a relative low sintering temperature (750 ∼ 800 °C). The thermal conductivity of Li2TiO3 ceramic sintered at 800 °C is calculated to be 3.48 W/m•K at room temperature, retaining 2.50 W/m•K at 773 K, which is comparable to the values in literatures. The results suggest the sintering activity of Li2TiO3 is greatly enhanced when alkaline hydrothermally treated P25 is used as titanium source.